2022
DOI: 10.1186/s12889-022-13592-0
|View full text |Cite
|
Sign up to set email alerts
|

School environment and obesity in adolescents from a Brazilian metropolis: cross-sectional study

Abstract: Background Childhood-juvenile obesity is a globally acknowledged public health issue. The school environment has been widely assessed because it is where adolescents stay longer during the day, and it may have impact on obesity. School became a crucial environment for obesity prevention in children and adolescents. The aim of the present study was to associate schools’ internal environment factors and its surrounding areas with obesity in adolescents from a Brazilian metropolis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…In recent years, there has been growing interest in the relationship between economic income and TMDs. 18,32,33 Economic income, as a component of socioeconomic status (SES), has been linked to a wide range of health outcomes, including chronic pain conditions. 34,35 Individuals with lower economic income may face various social and environmental stressors, including poverty, unemployment and inadequate access to health care, that can increase their risk for developing TMDs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, there has been growing interest in the relationship between economic income and TMDs. 18,32,33 Economic income, as a component of socioeconomic status (SES), has been linked to a wide range of health outcomes, including chronic pain conditions. 34,35 Individuals with lower economic income may face various social and environmental stressors, including poverty, unemployment and inadequate access to health care, that can increase their risk for developing TMDs.…”
Section: Discussionmentioning
confidence: 99%
“…This association is thought to be due to multiple factors, including increased stress levels, poor oral health habits, and a lack of access to dental care and treatment. 18,33 Stress is a known risk factor for TMD, and individuals living in poverty are more likely to experience chronic stress due to financial and social challenges. The physiological response to stress can lead to muscle tension in the face, neck and jaw, which can exacerbate TMD symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both children classified as overweight and obese were included in the category “overweight (including obesity),” according to the terminology used by Cole et al 38 , 39 We chose to analyze overweight and obesity together because this is a commonly used approach in nutritional epidemiology and because our power calculations were made based on prevalence of overweight/obesity combined. 40 - 42 For the sake of simplicity, this study will refer to the latter category as “overweight.” As a way of compensating the students and school’s effort, at the end of the survey each participating school received an individualized report with their students’ assessments. Individually, each student also received his/her assessment.…”
Section: Methodsmentioning
confidence: 99%
“…19 A cross-sectional study based on data from the Study on Cardiovascular Risk in Adolescents analyzed 2530 adolescents aged 12 to 17 years who were enrolled in public and private schools in Belo Horizonte City, Brazil and showed that obesity was present in 7.21% of the sample. 20 Another study analyzed the temporal variation in the incidence of overweight and abdominal obesity among adolescents from public schools in a capital in northeastern Brazil. This study included information from 3 cross-sectional surveys carried out in 2001, 2009, and 2017, with 2496 students aged 10 to 18 years living in the city of Salvador, Bahia, Brazil.…”
mentioning
confidence: 99%